Penerapan Konsep Green Construction pada Pelaksanaan Bangunan Gedung di Provinsi Jambi - Bimansyah, Willyam; Yamali, Fakhrul Rozi; Dony, Wari; Setiawan, Ari (Jurnal Talenta Sipil, 2025)
Global warming is a phenomenal issue today and is one of the challenges for the population in Indonesia.This environmental impact has an effect on global warming, for example, the reduction of green land due to development, waste of energy and building materials that are not environmentally friendly. Therefore, the concept of green construction was introduced in the scope of civil buildings. The purpose of this study is to obtain the percentage of contractors' understanding of the concept of green construction, and to obtain information about what obstacles are faced by contractors in Jambi Province in implementing the concept of green construction. This research was conducted using a questionnaire method, namely with data directly collected by researchers from the field. And for data processing, it is carried out by descriptive methods. The population was taken from contractors handling building projects in Jambi province in 2023 where the sample was 10 contractors. The results of the study show that the percentage of contractors' understanding of the concept of green construction is familiar with the term green construction. And the obstacle factor for contractors in Jambi province in implementing the concept of green construction is the lack of detailed rules regarding the concept of green construction and the lack of artenative materials and implementation in implementing green construction.